THE INFLUX OF UNQUALIFIED CHINESE WORKERS INTO INDONESIA: REGULATORY GAPS AND LOCAL LABOR MARKET IMPACTS - Wibhisana, Yohanes Putut; Kencono, Dilah (Fakultas Bahasa dan Budaya Universitas Darma Persada, 2026)
The influx of unqualified Chinese workers into Indonesia has become a pressing issue, raising concerns over employment fairness, regulatory integrity, and domestic workforce protection. Despite possessing limited skills, inadequate educational backgrounds, and no formal training, a significant number of Chinese nationals have successfully entered Indonesia's labor market, often occupying roles that could be filled by local workers. This study explores the root causes behind their migration, the mechanisms that facilitate their entry, and the resulting socio-economic impact on Indonesian labor. Relying on qualitative analysis of policy documents, interviews with workers from china who has arrived in Indonesia and who will go to Indonesia and still in China, the research identifies multiple push factors within China, including labor oversaturation, internal competition, and regional economic disparities, which drive individuals to seek opportunities abroad. At the same time, gaps in Indonesian labor regulations, weak enforcement, and opaque recruitment practices have created channels through which these unqualified workers are able to enter and remain in the country. The findings suggest that this phenomenon has contributed to wage suppression, increased competition for low-skilled jobs, and a growing sense of marginalization among native workers. The study concludes that more stringent labor screening, intergovernmental cooperation, and transparent employment oversight are critical to safeguarding Indonesia's labor ecosystem